Adapting Marketing Communication in the Repositioning of Therapeutic Products - Andi Juanna; Usep Suhud; Mohamad Rizan (Samudra Publisher, 2025)
This study aims to develop a contextual repositioning framework for traditional health products by integrating cultural roots and narrative authenticity into cross-cultural marketing strategies. The study highlights the challenges of aligning the values of traditional products with the dynamic preferences of modern health-conscious consumers, particularly in emerging markets such as Indonesia. A conceptual theory-building approach is employed, based on a comprehensive synthesis of 46 relevant publications from 2016 to 2025. The reviewed studies cover themes such as consumer acculturation, cultural storytelling, product repositioning, and health branding. The research reveals critical gaps in existing repositioning models, notably the lack of cultural context and the limited integration of emotional and narrative approaches in consumer engagement. Through integrative reasoning, this study proposes a conceptual framework that connects cultural roots, narrative authenticity, perceived health value, and consumer acceptance, mediated by cultural storytelling strategies. The proposed framework suggests that the repositioning of traditional health products requires a narrative-driven process, in which cultural roots and authenticity form the foundation of consumer engagement. By embedding local heritage values into brand narratives, companies can enhance consumer perceptions of health value, thereby fostering trust and acceptance. This conceptual contribution addresses theoretical gaps in existing cross-cultural marketing models and offers practical guidance for brand managers operating in culturally rich yet globally competitive health markets. The paper concludes with recommendations for future empirical research to validate the proposed propositions across diverse cultural contexts.